The concept of the rule of law and the European Court of Human Rights - Lautenbach, Geranne (Oxford : Oxford University Press, 2014)
The idea of the rule of law is a central, yet sometimes unclear notion within the international legal system. This text demonstrates its application by the European Court of Human Rights, against the background of theoretical accounts of the idea of the rule of law, and the differing approach of the UK France, and Germany.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Rule of law -- Great Britain; Rule of law -- France; Rule of law -- Germany; European Court of Human Rights